Case Report: Watching and Waiting? A Case of Incomplete Glenosphere Seating With Spontaneous Reversal in Reverse Shoulder Arthroplasty. (August 2020) - MacAskill, Micah L; Thomas, Rachel J; Barnes, Leslie A
Introduction: Reverse shoulder arthroplasty is a useful procedure with broadening applications, but it has the best outcomes when used for rotator cuff tear arthropathy. However, this procedure is not without complications. While scapular notching and aseptic loosening are more common complications that have been extensively studied in the literature, dissociation of the glenoid component and incomplete glenosphere seating has not received much attention. Specifically, little research has explored appropriate management of incomplete seating of the glenosphere component, and no gold standard for treatment of this complication has emerged. Methods: In the case described here, an elderly patient with an incompletely seated glenosphere component post-operatively opted to pursue conservative management in order to avoid revision surgery if possible. Results: The partially engaged, superiorly directed components in this case exhibited spontaneous complete and symmetric seating of the glenosphere between six and twelve months post-operatively, indicating that conservative management of this complication in low-demand patients may be a viable option to avoid the risks associated with revision surgery. Conclusion: Further research should be pursued to explore what patient and prosthesis design factors may be suited to observation with serial radiographs when incomplete seating of the glenosphere component occurs.